Photodissociation of oriented HXeI molecules generated from HI-Xen clusters - Nahler, N.H.; Baumfalk, R.; Buck, U.; Bihary, Z.; Gerber, R.B.; Friedrich, B. (Journal of Chemical Physics, 2003)
We report the production in the gas phase of ionically bound HXeI molecules. The molecules are generated by the photodissociation of HI molecules in large Xen clusters and are identified from the asymmetry of the detected H atom fragments arising from the dissociation of oriented HXeI. The orientation, resulting from a synergistic action of a pulsed laser field with a weak electrostatic field, is quite pronounced, due to a large ratio of the polarizability anisotropy to the rotational constant of HXeI.
EPrint Processing Status: Publisher does not permit full text to be deposited